FROM RIVALRY TO RITUAL: SUNGKEMAN AS A STRATEGIC POLITICAL COMMUNICATION TOOL IN INDONESIAN POLITICS - Khaz, Fitra Hadi; Erinaldi, Erinaldi; Refdi, Refdi; Mirza, Dede; Saputra, Trio (Universitas Padjadjaran, 2026)
This study explores the overlooked phenomenon of “political sungkeman “ as a culturally rooted yet politically strategic gesture performed by Prabowo Subianto toward Joko Widodo (Jokowi) during Indonesia’s 2019 and 2024 presidential elections. While symbolic gestures have been widely studied in global political communication, limited attention has been paid to how localized traditions like sungkeman are adapted to mitigate polarization and influence public perception in highly mediated electoral contexts. Utilizing a qualitative literature review combined with political discourse and media framing analysis, this study investigates the role of sungkeman through five analytical dimensions: political reconciliation, cultural symbolism, image strategy, public response, and media narrative. The findings reveal that sungkeman is employed as a calculated political communication tool that evokes familiarity, fosters reconciliation at the elite level, and helps craft a respectful public image. However, public reactions remain divided along cultural, social, and political lines, reflecting tensions between perceived sincerity and performative intent. The widespread use of digital platforms and entertainment politics further amplifies or challenges the authenticity of this gesture. This research contributes to the theoretical development of political semiotics by providing a culturally specific case from the Global South, demonstrating how traditional practices are repurposed for modern political goals. The implications extend to the broader discourse on democracy, suggesting that culturally resonant communication can foster national unity, but only when grounded in genuine accountability and transparent leadership.